Tourism and Human Rights: Examining the Exploitation of Workers in Indonesia’s Tourism Industry (Indonesian Tourism Justice Review, 2024)
The tourism industry in Indonesia, while a major economic driver, has been criticized for labor exploitation and violations of workers’ rights, particularly in high-demand tourist regions such as Bali and Jakarta. This paper explores the human rights implications of labor practices in the Indonesian tourism sector, focusing on exploitation issues such as low wages, long working hours, lack of job security, and poor working conditions. By examining case studies from various hospitality and service sectors, this research reveals the systemic exploitation of tourism workers, particularly among women and migrant laborers. Drawing on international labor standards and local labor laws, the study highlights the disconnect between legal protections and the realities of workers on the ground. The paper critiques both governmental and corporate responses to these issues and assesses their efficacy in improving labor conditions. It further discusses the role of human rights organizations and trade unions in advocating for the rights of tourism workers. The paper concludes with recommendations for the implementation of stricter labor regulations, the establishment of fair labor practices, and the creation of a sustainable tourism model that prioritizes the welfare of workers.